From social climbing to “achoramiento”: anomic means of social ascension - Medina, Oswaldo (1994)
The article deals with the popular concept of "achoramiento" as a mean of social ascension, and opposes it to that more classical of "arribismo" (social climbing). It claims that both concepts are a product of their historical and economical context: rigid, patriarchal and personalized, the first one (before 1970); convulsed and without norms the other (after 1970). It maintains, at the end, that the "arribismo-strategy" tums out to be inefficient to cope with the new problems due to migration and generalized social crisis, thus inducing social actors of all classes to behave themselves in a way the author calls "achorada", defined primarily as the type of behavior which recognizes neither norms nor authority.